A new perspective on Wendan decoction: attenuation of CUMS-induced anxiety in mice by regulating gut microbiota and neuroinflammation - Guo, Zixuan; Wang, Qianqian; Cao, Yunge; Wang, Baiyan; Zhang, Boyi; Huang, Jiawei; Niu, Yuanyuan; Huang, Junhong; Wang, Zilong; Feng, Shuying (Frontiers in Microbiology, 2025)
PurposeTo study the effects of Wendan decoction (WDD) on anxiety in mice that have been exposed chronic unpredictable mild stress (CUMS) and to look into the underlying mechanisms from the perspective of regulating neuroinflammation and gut microbiota.MethodsThe CUMS program was administered to C57BL/6 J mice to mimic chronic exposure to persistent and uncontrollable stresses. Alterations in anxiety-like behaviors were documented via behavioral tests. After euthanasia, pro-inflammatory cytokines in colonic and hippocampal tissues were detected using ELISA kits. Using H&E staining and immunofluorescence staining, morphological alterations and neuroinflammation in the hippocampus were assessed. To assess the impact of WDD on gut microbiota, 16S rDNA gene sequencing was done.ResultsMice in the CUMS group showed less food intake and less weight gain. Behavioral assessments revealed increased behaviors that resembled anxiety. WDD therapy reduced the mice’s anxiety-like behaviors while increasing their body weight and food intake. In addition, WDD treatment significantly enhanced gut microbiota diversity and effectively modulated composition. WDD also reduced pro-inflammatory cytokine levels in colonic and hippocampal tissues, alleviating intestinal inflammation and neuroinflammation.ConclusionWDD ameliorates CUMS-induced anxiety by modulating gut microbiota and attenuating neuroinflammation in mice.